Is Transracial the Same as Transgender? The Utility and Limitations of Identity Analogies in Multicultural Education. (2nd July 2016) - Tran, Vu T.; Johnston-Guerrero, Marc P.
Abstract : In June 2015, Melissa Harris-Perry infamously analogized the possibility of trans-Black identity to the reality of transgender identity. Such analogies happen often and are used mostly for the benefit of learning about a less familiar form of identity. Building from a recent article by Suthakaranm, Filsinger, and White (2013 ) that presented a compelling argument for the use of analogies as an experiential learning tool in multicultural education, we advance the conversation by distinguishing a particular form of analogies: identity analogies. We explore the benefits and challenges of utilizing identity analogies as a tool for multicultural educators within U.S. higher education.